(untitled) (Journal of Hama University, 2021)
Pain is an unpleasant human experience, often associated with underlying medical conditions, and a key reason for individuals experiencing pain to seek medical advice. However, the pain experience is unique and subjective, and affects people’s quality of life, as well as impacting on their concerned family members. This has been identified as a significant clinical problem. relieving pain is a central goal of many oncology nursing interventions, Optimal pain management requires adequate knowledge, a positive attitude, and competent pain assessment measures. The purpose of the present study was to Assessment Of Knowledge And Attitudes Of Nursing Staff Regarding To Pain Management Among Cancer Patients At Tishreen University Hospital . The sample consisted of 85 nurses work in the chemotherapy center At Tishreen University Hospital. The Nurses’ Knowledge and Attitudes Survey Regarding Pain management was used to measure the nurses’ pain management knowledge and attitudes. The study was descriptive survey, Data were analyzed by using descriptive statistics. The results showed that the highest percentage of nurses 83.5%, have a poor level of knowledge and a negative attitude orientation towards pain management. While 15.3% of them had a moderate level of knowledge and a neutral attitude towards pain management. A very small percentage 1.2%, have good knowledge and a positive attitude towards pain management. The results of this study could be useful to institutions involved in patient care and teaching of pain management.